The role of nuclear material in the transfer of immunological information: I. Nuclei from rat lymphocytes stimulated with mitogens - Lewis, C. M. (1973)
It has been shown that nuclei from lymphocytes stimulated with either PHA (Pegrum, Perera and Thompson, 1972), Con A or pokeweed have marked mitogenic properties. The ability of various lymphoid tissues to respond to such nuclear material differs from the response they show to the mitogens themselves. Nuclei from rat lymphocytes stimulated with PHA or Con A will activate the lymphocytes from either spleen, bone-marrow or thymus whilst nuclei from pokeweed-stimulated cells appear capable of stimulating only the bone-marrow-derived lymphocytes. It is suggested that the ability of the nuclear material from PHA or Con A-stimulated lymphocytes to induce mitogenesis in bone-marrow-derived cells may relate to cellular co-operation; `T' cell processing being a prerequisite for `B' lymphocyte triggering.